Isolation and characterization of bacteria from the gut of Irish honey bees for potential probiotic applications - Pimentel Bentancurt, Diana Carolina (2023)
Honey bees are essential for pollination. Without the work they do, biodiversity and food security would be at risk.Currently the population of these insects has decreased due to the interaction of various factors such as pesticides andseveral diseases that affect them, among others.The gut microbiota of honey bees is diverse and performs several important functions that significantly contribute totheir nutrition, digestion, defense against pathogens, and insecticides resistance, therefore improving their immunesystem and health. This microbiota depends on genetic, geographic and environmental factors. The aim of this workwas to isolate bacteria from the gut of Irish honey bees and to carry out their characterization, molecularidentification, resistance to antibiotics and antimicrobial activity in search of potential probiotics that could mitigatethe negative effects of agrochemicals and improve defense against pathogens.For this reason, honey bees from five different colonies were collected and bacteria were isolated in MRS,MRS-cysteine and Tryptone soya agar culture medium. The characterization was performed by means of Gramstaining, morphological observations and catalase test. Molecular identification was carried out by 16s rRNAsequencing. The susceptibility of the isolated bacteria to antibiotics was tested using the micro-dilution method.Antibacterial activity against an indicator strain were evaluated by deferred antagonism assays. Forty strains wereisolated from the gut of Irish bees. Analysis of the 16S rRNA gene sequence indicated that some bacteria belong toLactobacillus helsingborgensis, L. apis, Apilactobacillus kunkeei, among others. Almost all bacteria were Gram-positiveand catalase negative differing in colony morphology and size. Based on the antibiotic results, most of the bacteriawere susceptible to all of the tested antibiotics, according to the European Food Safety Authority breakpoints.The MIC ranged between 0.016-1.23 mg/L for erythromycin, 0.14-5.97 mg/L for tetracycline, and 0.4-3.7 mg/L forchloramphenicol. Few bacteria were found to be resistant to ampicillin. Some of strains showed antimicrobial activityagainst the indicator strain. The results suggest that some of the bacteria isolated from the bee gut have potentialapplication for probiotics due to their safety (generally regarded as safe GRAS status), non-resistance to antibiotics,and their antimicrobial activity.